Pengaruh Metode Token Economy Terhadap Aktifitas Perawatan Diri pada Pasien Defisit Perawatan Diri: The Influence of Token Economy Method on Self-Care Activities in Patients with Self-Care Deficits - Heppi Sasmita; Rizka Mahdairta; Asterina (NERS Jurnal Keperawatan, 2012)
Self-care deficit is an impaired ability to perform self-care activities. Lack of self-care results from changes in thought processes, leading to a decline in the ability to perform self-care activities. The token economy method is a behavior modification technique that involves giving a token or gesture as soon as each target behavior appears. This study used a pre-experimental design with a pretest-posttest one group approach to patients with self-care deficits in the Prof. HB. Sa’anin Mental Hospital, Padang, involving a total of 15 people from 19 November to 9 December 2011. The aim was to determine the effect of the token economy method on self-care activities. Sampling was conducted using a total sampling technique. The research variables were the token economy method and self-care activities. Data collection was done by measuring the respondents' self-care activities before and after treatment using an observation sheet. Data analysis was performed using SPSS with the Wilcoxon test. Results showed a significant effect of the token economy method on increasing self-care activities, with statistical test results showing p < 0.05. It is expected that Prof. HB Sa’anin Mental Hospital, Padang, will use the token economy method as a means to address self-care deficits.